Is an unbiased science of religion impossible? - Hödl, Hans Gerald (Religio, 2012)
In this paper I present a critical discussion of the essay "Religious Studies as a Scientific Discipline: The Persistence of a Delusion" by Luther H. Martin and Donald Wiebe (Religio: Revue pro religionistiku 20/1, 2012, 9-18). The focus of the argumentation lies on the assumptions the authors adopt. The authors' understanding of the nature of science, concerning both methodology and the theory of science, is taken into consideration, and their definition of religion is discussed on the background of other definitions available. As an outcome, four questions are formulated that should be taken into account in further discussions of the topic. Finally, some remarks concerning the nature of religions are added. I think that the "Tylorian" definition of religion used by the authors is too narrow and I opt for an understanding of religion as based on the central questions facing human beings about the meaning of life that religions purport to give answers to. The persistence of religion is better explained by the ability of the human being to ask such questions than by the evolutionarily acquired proclivity towards "agent causality". I try to show that this can be achieved at the level of meta-language that is clearly delineated from religious object language.